2014
DOI: 10.1371/journal.pone.0087974
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels Vary during Antiviral Treatment but Are Unable to Predict Treatment Outcome in HCV Genotype 1 Infected Patients

Abstract: BackgroundDifferent parameters have been determined for prediction of treatment outcome in hepatitis c virus genotype 1 infected patients undergoing pegylated interferon, ribavirin combination therapy. Results on the importance of vitamin D levels are conflicting. In the present study, a comprehensive analysis of vitamin D levels before and during therapy together with single nucleotide polymorphisms involved in vitamin D metabolism in the context of other known treatment predictors has been performed.MethodsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
(69 reference statements)
1
17
0
1
Order By: Relevance
“…Therefore, 11 studies, comprised of 7 published articles [5][6][7][8][9][10][11] and 4 conference abstracts [20][21][22][23], involving 2605 patients with chronic HCV infection, were included in the meta-analysis (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 11 studies, comprised of 7 published articles [5][6][7][8][9][10][11] and 4 conference abstracts [20][21][22][23], involving 2605 patients with chronic HCV infection, were included in the meta-analysis (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…While some studies found an independent association between a higher baseline 25(OH)D level and SVR in HCV genotype 1/4/5 infection [5][6][7] and genotype 2/3 infection [8], others failed to find any relationship between baseline vitamin D level and treatment response [9][10][11]. These discordant results have led to uncertainty whether the baseline vitamin D level has any influence on SVR to PEG-IFN plus RBV antiviral therapy in chronic HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the present study, rs7944926 was analyzed. Previous studies have shown that genotypes with the G allele for DHCR7 (rs7944926), G allele for CYP2R1 (rs10741657), G allele for GC (rs2282679), and T allele for CYP27B1 (rs10877012) are risk factors for low serum 25(OH) D 3 levels [Lange et al, 2011[Lange et al, , 2012[Lange et al, , 2013Grammatikos et al, 2014]. A non-carrier of the T allele for VDR gene (rs2228570) is also considered a risk factor for low serum 25(OH) D 3 levels [Garcia-Martin et al, 2013].…”
Section: Vitamin D-related Gene Polymorphismsmentioning
confidence: 99%
“…Several vitamin D-related gene polymorphisms were reported to contribute to SVR [Lange et al, 2011[Lange et al, , 2012Baur et al, 2012;Falleti et al, 2012;Garcia-Martin et al, 2013;Grammatikos et al, 2014]. We analyzed whether these polymorphisms could influence serum 25(OH) D 3 levels.…”
Section: Association Between Vitamin D-related Gene Polymorphisms Andmentioning
confidence: 99%
See 1 more Smart Citation